RETRACTED: Circular RNA Circ-0002570 Accelerates Cancer Progression by Regulating VCAN via MiR-587 in Gastric Cancer - Yang, Lei; Zhou, Yong-ning; Zeng, Miao-miao; Zhou, Nan; Wang, Bin-sheng; Li, Bo; Zhu, Xiao-liang; Guan, Quan-lin; Chai, Chen (Frontiers in Oncology, 2021)
Background Circular RNAs (circRNAs) are closely associated with the occurrences and progress of gastric cancer (GC). We aimed to delve into the function and pathological mechanism of Circular RNA-0002570 (circ-0002570) in GC progression. Methods CircRNAs differentially expressed in GC were screened using bioinformatics technology. The expression of circ-0002570 was detected in GC specimens and cells via qRT-PCR, and the prognostic values of circ-0002570 were determined. The functional roles of circ-0002570 on proliferation, migration, and invasion in GC cells were explored in vitro and in vivo. Interaction of circ-0002570, miR-587, and VCAN was confirmed by dual-luciferase reporter assays, Western blotting, and rescue experiments. Results Circ-0002570 expression was distinctly increased in GC tissues compared to adjacent normal specimens, and GC patients with higher circ-0002570 expressions displayed a short survival. Functionally, knockdown of circ-0002570 resulted in the inhibition of cell proliferation, migration, and invasion, and suppressed tumor growth in vivo. Mechanistically, miR-587 was sponged by circ-0002570. VCAN expression in NSCLC was directly inhibited by miR-587. Overexpression of circ-0002570 prevented VCAN from miR-587-mediated degradation and thus facilitated GC progression. Conclusion The circ-0002570-miR-587-VCAN regulatory pathway promoted the progression of GC. Our findings provided potential new targets for the diagnosis and therapy of GC.